Developmental changes in and the relationship between psychological resilience and mental health problems in adolescents relocated for poverty alleviation in the context of COVID-19 epidemic prevention and control - Zhu, Hai; Song, Juan; Zhang, Rong; Wang, Benbin; Shen, Xiaosong (Frontiers in Public Health, 2023)
Background:Adolescents relocated for poverty alleviation have considerable mental health problems (MHPs) in the context of changing living environments and COVID-19 epidemic prevention and control, and psychological resilience (PR) is closely related to MHPs. Existing studies have mainly used cross-sectional research to investigate the relationship between PR and MHPs using PR as a predictor variable. Objective: This study investigated developmental changes in the PR and MHPs of relocated adolescents as well as the relationship between these factors.Methods: A longitudinal study was conducted to assess the PR and MHPs of 1284 relocated adolescents. Data were collected at approximately 12-month intervals at three time points: spring of 2020 (T1), spring of 2021 (T2), and spring of 2022 (T3). The collected data were analyzed using SPSS 25.0 and Mplus 8.1 and methods such as latent growth models and cross-lagged regression analysis. Results:(1) The PR level of relocated adolescents showed an overall increasing trend (slope = 0.16, p < 0.01), while the MHPs showed an overall decreasing trend (slope = -0.03, p <0.01). (2) The initial PR level differed significantly from the initial MHPs level (β = -0.755, p = 0.00), and the rate of change in PR differed significantly from the rate of change in MHPs (β = -0.566, p = 0). The initial MHPs level differed significantly from that of PR (β = -0.732, p = 0.00), and the rate of change in MHPs differed significantly from the rate of change in PR (β = -0.514, p = 0.00). (3) Among the three sets of measurements of PR and MHPs, there were significant pairwise differences. Conclusion:(1) The PR level of relocated adolescents increased over time, and the MHPs of relocated adolescents decreased over time. (2) The initial PR level of relocated adolescents had a negative predictive effect on the initial MHPs level, and the rate of change in PR had a negative predictive effect on the rate of change in MHPs. (3) The PR and MHPs of relocated adolescents exhibited a bidirectional, mutually influencing relationship.